A Prospective Study to Evaluate Awareness among Healthcare Personnel about Medication Errors in a Tertiary Care Teaching Hospital - Kumar, Shiv; Ramankutty, Abhinand Chirayil; Jayachandran, Shravan (Indian Journal of Pharmacy Practice)
Objectives: To evaluate awareness among health care personnel about medication errors in a tertiary care teaching hospital. Methods: A questionnaire comprising of 17 questions pertaining to different aspects of medication error was prepared. The questionnaire was distributed to 171 healthcare professionals of various departments in the hospital. Respondents of the questionnaire were restricted to one sitting for answering the entire questionnaire and they were not allowed to consult with anyone for the purpose of answering the questions. Data was compiled and analysed. Results: It has been found that 15.78%, 32.15%, 19.29% and 30.72% of respondents were having excellent, good, average and poor knowledge respectively regarding the fundamentals of medication error. Knowledge regarding reporting medication errors was excellent in 26.37%, good in 26.90%, average in 24.56% and poor in 32.16% of respondents. About 63.15%, 18.12%, 7.60% and 11.09% of the healthcare professionals were excellent, good, average and poor for recommending or opine about the betterment of the system for reporting medication errors. Among the different healthcare professionals, Pharmacy personnel’s are having superior knowledge about the medication error, its reporting system and the suggestion for betterment of its reporting system followed by Nursing and Medical professionals. Conclusion: The present study reveals that all the healthcare professionals are having good to average awareness about medication errors and its reporting system and all the healthcare professionals are strongly suggesting for the betterment of the reporting system.
Keywords: Awareness; Healthcare professionals; Medication errors; Questionnaire; Reporting system.